Cognitive Impairment in Genetic Parkinson's Disease. (30th December 2021) - Planas-Ballvé, A.; Vilas, D.
Abstract : Cognitive impairment is common in idiopathic Parkinson's disease (PD). Knowledge of the contribution of genetics to cognition in PD is increasing in the last decades. Monogenic forms of genetic PD show distinct cognitive profiles and rate of cognitive decline progression. Cognitive impairment is higher in GBA- and SNCA -associated PD, lower in Parkin- and PINK1 -PD, and possibly milder in LRRK 2-PD. In this review, we summarize data regarding cognitive function on clinical studies, neuroimaging, and biological markers of cognitive decline in autosomal dominant PD linked to mutations in LRRK2 and SNCA, autosomal recessive PD linked to Parkin and PINK1, and also PD linked to GBA mutations.